P066 Polarity-specific modulation of central pain processing by transcranial direct current stimulation. Issue 3 (March 2017) - Naegel, S.; Biermann, J.; Theysohn, N.; Diener, H.-C.; Obermann, M.; Holle, D.
Abstract : Background: Transcutaneous direct current stimulation (tDCS) is a known tool for inducing changes in cortical excitability influencing motor as cognitive functions. Previous studies suggest that application of tDCS might be a therapeutic approach for pain disorders as well. Objective: The aim of the study was to investigate pain-related changes in cerebral activation pattern and its modulation by direct current stimulation. Methods: Thirteen right-handed healthy participants received 20 min of tDCS applied over primary motor cortex (M1) under three different conditions which are anodal-tDCS, cathodal-tDCS, and sham-tDCS in a blinded cross-over design. Afterwards tDCS neural response to electric trigeminal pain stimulation was investigated using a block designed fMRI. Between the three tDCS conditions a time interval of at least 2 months was kept. Results: All pain stimulation showed distinct activation pattern in the established brain areas of pain processing. Following anodal tDCS increased activation was detected in different part of the pain processing network including thalamus, basal ganglia, cingulate cortex, dorsolateral prefrontal cortex, and amygdala while cathodal t-DCS showed decreased BOLD response in these pain processing areas. Behavioral data were not changed irrespective of tDCS stimulation mode. Discussion: Our study shows polarity-specific modulation of cerebral pain processing, which are in line with previous electrophysiological data. Anodal tDCS leads to an increased activation of the central pain-network compared to cathodal tDCS. Our results contribute to a network-based understanding of the underlying mechanism in tDCS.